Treatment Outcomes of Esophageal Cancer in Malawi: An Analysis of Overall Survival and Patient-Reported Outcomes - Gift Mulima (JCO Global Oncology, 2025)
PURPOSEEsophageal squamous cell carcinoma (ESCC) is a prevalent cancer in eastern Africa. Optimal management strategies in eastern Africa have not been well established. This study aimed to evaluate ESCC treatment outcomes at Kamuzu Central Hospital (KCH), a national cancer center in Malawi.METHODSThis prospective, observational, cohort study was conducted as part of a multicenter collaboration within the African Esophageal Cancer Consortium (ClinicalTrials.gov identifier: NCT05177393). Patients who presented to KCH with esophageal cancer (EC) were recruited from June 2021 to December 2022. Data on patient and treatment characteristics were collected using interviews and chart review. Mobile phone outreach was used to assess patient-reported outcomes (PROs). PROs were analyzed using linear mixed modeling. Kaplan-Meier method with log-rank test and Cox proportional hazards regression were used to evaluate overall survival by treatment group.RESULTSA total of 148 of 150 eligible patients enrolled. Of 114 with biopsy-proven EC, 97% (n = 111) had ESCC. Most were documented as having localized disease; however, 56% did not complete staging imaging. Forty-seven percent received supportive care, 30% self-expandable metallic stent (SEMS), 20% chemotherapy, and 3% SEMS plus chemotherapy. SEMS was associated with the highest proportion experiencing dysphagia improvement (SEMS 68% v chemotherapy 63% v supportive care 39%). Twelve-month survival rate was the highest in the chemotherapy arm (29% v supportive care 19% v SEMS 6%, log-rank P = .018).CONCLUSIONESCC remains a highly fatal malignancy in Malawi. Most patients at KCH are treated with SEMS or supportive care. Although data must be interpreted with caution given likely confounding, chemotherapy was associated with the highest 12-month survival rate as compared with SEMS and supportive care, whereas SEMS was associated with the highest likelihood of improved dysphagia.